Problems Faced by the Cashew Exporters in Kerala, India: A Recent Study - Haritha Paul; K. N. Ushadevi (Research Highlights in Agricultural Sciences Vol. 1, 2022)
The study aims to analyse the issues faced by cashew exporters in Kerala, given the prospective future of the cashew export market. In the Kollam district of Kerala, 65 cashew exporters (who have been continually exporting cashew for the last five years) were chosen at random for the primary survey, which was done using a pre-tested structured questionnaire. To analyse the problems faced by the cashew exporters in Kerala, Garrett’s ranking technique was used. High processing costs, the inability to achieve Standard Input-Output Norms (SION), threats of foreign entrants into the domestic market, a reduction in international share, the concentration of processing in large sectors, and the exploration of new markets are among the major issues that cashew exporters face, according to the study. As a result, protective policies such as increasing exportable grades at a ratio of 1:6, removing the basic customs duty imposed on imported cashew, and increasing the government’s export incentives would help to alleviate the cashew industry’s challenges.